Risk Assessment of Toxic Heavy Metal Exposure through Medicinal Herbs in the Indian State of West Bengal - Hazra, Avijit; Hazra, Alok Kumar; Jana, Swapan Kumar; Sur, Tapas Kumar (Journal of Current Toxicology and Venomics, 2024)
BackgroundMore than 80% of the world's population uses herbal remedies in some form. Heavy metal contamination and the attendant health risks of Indian herbal medicines are not adequately documented.ObjectiveThis study aimed to investigate the health risks associated with four common heavy metal contaminants, namely lead, arsenic, cadmium, and mercury, present in raw medicinal herbs cultivated or growing wild in the West Bengal state of India.MethodsA total of 197 raw herbs obtained from herbal medicine practitioners or wild plant collectors from 16 districts spread across 3 geographical zones (south, central, north) of West Bengal were analyzed. In accordance with AOAC specifications, all samples were dried in a hot air oven, ground into a coarse powder, and then processed and analyzed for heavy metals through atomic absorption spectrometry. The mean concentrations were estimated along with standard deviations, overall, zone-wise, and according to the botanical part tested. The standardized human health risk indices were calculated from the results.ResultsSignificant amounts of heavy metals were found in the herb samples analyzed in the order: lead in 150 samples (76.1%), arsenic in 84 (42.6%), cadmium in 77 (39%), and mercury in 47 (23.8%). Central zone samples had the highest concentrations of lead (10.06 µg/g), arsenic (0.62 µg/g), and cadmium (0.54 µg/g), while the greatest amount of mercury (0.08 µg/g) was obtained in herbs from South zone. There were also considerable variations with respect to the source of the botanical part. Lead and cadmium concentrations showed a significant positive correlation (r = 0.588). Although risk assessment using standardized measures indicated some risk, the human Hazard Index (HI) was less than 1 for all metals, indicating that it was mostly safe to use the herbs in the short-term. However, the risk of health issues from prolonged use still remains.ConclusionSignificant contaminations were identified, but exposure would mostly be within acceptable risk levels at present. However, since risk would be cumulative over time, programs need to be in place to monitor pharmaceutical herb safety, identify local sources of pollution, and take appropriate remedial action.
Keywords: mercury